Implications of the Deep Learning Approach in Learning the Qur'an and Hadith at Madrasah Aliyah Miftahul Ulum Punggur Besar - Roziqin, Roziqin; Wahab, Wahab (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the application of the deep learning approach in Al-Qur'an Hadith learning at Madrasah Aliyah Miftahul Ulum Punggur Besar, as well as to examine the supporting factors, obstacles, and implications for the quality of learning. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that teachers have designed learning plans that integrate the analysis of the meaning of verses and hadith, reflective activities, case studies, and the use of simple digital media, thereby encouraging students to think critically, reflect on values, and connect religious teachings with the context of real life. Supporting factors for the implementation of deep learning include teachers' readiness to innovate, students' openness to reflective methods, and the characteristics of Al-Qur'an Hadith material that support deep meaning, while obstacles include time constraints, teachers' administrative burdens, inadequate digital facilities, and variations in student abilities. The research findings confirm that the successful implementation of deep learning is highly dependent on institutional support, teacher training, strengthening of digital facilities, flexibility in learning time, and systemic integration into the curriculum and lesson plans. Overall, the deep learning approach has proven to be relevant and strategic in shaping reflective, contextual Al-Qur'an Hadith learning that is oriented towards strengthening student character in line with the demands of 21st-century education.